Activities between activities of focus—Relevant when assessing DNA transfer probabilities. (December 2015) - van Oorschot, R.A.H.; McColl, D.L.; Alderton, J.E.; Harvey, M.L.; Mitchell, R.J.; Szkuta, B.
Abstract: Consideration of the indirect transfer of 'touch DNA' is increasingly becoming part of criminal investigations. Focus is often concentrated on the actions relating to the pick-up of the relevant DNA and key actions associated with transfer to the exhibit from which the sample in question was collected. There is often a time lapse between such actions. As any contact can influence the gain and/or loss of DNA, it is relevant to have an awareness of what hands touch during everyday activities in order to assist consideration of what may be occurring during potential time lapses within contemplated scenarios. To gain an appreciation of the manner and frequency of hands contacting various surfaces during everyday activities, we analysed several videos of individuals performing a variety of general activities. The findings indicate that several items are touched over a relatively short period of time. Appreciation and consideration of general activities that may have occurred between key focus activities are necessary to assess any impact these may have on what is deposited at the final collection site. The information this provides is imperative when weighting alternative transfer scenario propositions.